Foxtail millet [Setaria italica (L.) P. Beauv.] grown under nitrogen deficiency exhibits a lower folate contents - Wang, Yuan; Wang, Jin-song; Dong, Er-wei; Liu, Qiu-xia; Wang, Li-ge; Chen, Er-ying; Jiao, Xiao-yan; Diao, Xian-min (Frontiers in Nutrition, 2023)
Foxtail millet, a rich source of folates, is cultivated on infertile lands, for which N deficiency is the major issue. Environments have a significant influence on cereal folate levels. It is unknown whether N deficiency modulates folate levels. We investigated folate derivatives of 29 diverse foxtail millet cultivars under two N regimes (0 and 150 kg N ha-1) for two years to explore folate potential grown under low N. N deficiency reduced the contents of total folate and most derivatives. N affected folate content stronger than that of the cultivar genotype. Folate content of enriched folate cultivars was reduced by N deficiency obviously. Structural equation models (SEMs) revealed that N fertilization had a positive indirect effect on grain folate through influencing plant N and K accumulation, which indicated much attention should be paid to N management when foxtail millet was cultivated in infertile soil, to ensure foxtail millet folate contents.